Lichenoid lesions of the upper labial mucosa: a systematic review and a report of a new case with extensive follow-up. (2nd January 2023) - Halonen, Maisa; Siponen, Maria
Abstract: Objectives: The paper reports the demographic characteristics of patients with lichenoid lesions affecting only the upper labial mucosa, with or without associated lesions in the maxillary anterior gingiva, alongside the lesions' clinical and histopathological features, treatment, follow-up and prognosis. Also, a new case with lengthy follow-up is presented. Materials and methods: A systematic review was performed in line with PRISMA guidelines. The literature search sources were PubMed, Scopus and Web of Science. Results: In all, 26 patients (21 women, 5 men) were included in the review. 80.8% ( n  = 21) of the labial lesions were clinically erythematous and 19.2% ( n  = 5) were accompanied by white striations. The gingiva was affected in 46.2% of cases. All patients (100%, n  = 24) reported symptoms. All of the lesions presented histological features of lichenoid inflammation. Granulomas were noted in 65.4% ( n  = 17) of the lesions. Topical corticosteroid was the most frequent therapy (89.5%, n  = 17). Conclusions: Lichenoid lesions found solely in the upper labial mucosa, with or without adjacent gingival lesions, are rarely reported in the literature, and the reporting is often incomplete. A definitive aetiology could not be established for the lesions. Likewise, there is little information about this condition's long-term prognosis.